Experimental induction of mouthrot in Atlantic salmon smolts using Tenacibaculum maritimum from Western Canada. Issue 8 (14th May 2018) - Frisch, K; Småge, S B; Vallestad, C; Duesund, H; Brevik, Ø J; Klevan, A; Olsen, R H; Sjaatil, S T; Gauthier, D; Brudeseth, B; Nylund, A
Abstract: Mouthrot, or bacterial stomatitis, is a disease which mainly affects farmed Atlantic salmon, ( Salmo salar, L.), smolts recently transferred into salt water in both British Columbia (BC), Canada, and Washington State, USA. It is a significant fish welfare issue which results in economic losses due to mortality and antibiotic treatments. The associated pathogen is Tenacibaculum maritimum, a bacterium which causes significant losses in many species of farmed fish worldwide. This bacterium has not been proven to be the causative agent of mouthrot in BC despite being isolated from affected Atlantic salmon. In this study, challenge experiments were performed to determine whether mouthrot could be induced with T. maritimum isolates collected from outbreaks in Western Canada and to attempt to develop a bath challenge model. A secondary objective was to use this model to test inactivated whole‐cell vaccines for T. maritimum in Atlantic salmon smolts. This study shows that T. maritimum is the causative agent of mouthrot and that the bacteria can readily transfer horizontally within the population. Although the whole‐cell oil‐adjuvanted vaccines produced an antibody response that was partially cross‐reactive with several of the T. maritimum isolates, the vaccines did not protect the fish under the study's conditions.